Leadership in Action: Leveraging Diversity: It Takes a System - Shipp, Pamela; Davison, Carl (Center for Creative Leadership, 2001)
Too many organizations and leaders overlook an ace in the hole for creating value: managing the diversity of the workforce in a way that maximizes the talents and intellectual capital of all their employees.